Peningkatan Kemampuan Melempar Bola Menggunakan Sasaran, Metode Bermain Siswa V SD Negeri 211/9 Mendalo Darat - Ilham Ilham; Sri Murniati; Mhd. Usni Zamzami Hasibuan (Indonesia Sport Journal, 2019)
This study aims to improve the ability to throw the ball using the target with the method of playing on the students of class V SD Negeri 211/9 Mendalo Darat. This study is a classroom action research carried out within two cycles, each cycle with twice face to face and each face to face with allocation time 105 minutes. Subjects in this study are students of class V amounted to 21 students. Data analysis technique used is descriptive qualitative with a narrative. The results of this study indicate that capacity building efforts throwing a ball using a target with a play method can increased. Improvement of learning process includes improvement of learning teachers, increased student participation, and student learning outcomes. Goal of completeness the skill of throwing the ball using the target on the students in this study is achieving value KKM 70, but students can go through targets than expected by researchers ie 75%, this can be proven from the initial data that only reached 42.8%. Thus the action of skill-throwing skills using the target with the method of play given to the students of class V SD Negeri 211/9 Mendalo Darat can said successful.